Analisis Alih Kode Dan Campur Kode Pada Proses Pembelajaran Bahasa Indonesia Di Kelas X Dan XI Smk Muhammadiyah 2 Surakarta Tahun Pelajaran 2015/2016 - Zuliawati, Hendri (2016)
Code switching and code-mixing often occur in a variety of community conversations, code switching and code-mixing can occur in all societies, a person's social status can not prevent the occurrence of code switching and code-mixing often called multi language. This study aimed to describe the code switching and code-mixing contained in learning Indonesian in class X and XI SMK Muhammadiyah 2 Surakarta academic year 2015/2016. This study is a qualitative descriptive study. The subject of this research that Indonesian teachers and students of class X and XI in SMK Muhammadiyah 2 Surakarta academic year 2015/2016. Object of research are aspects of the research subjects who were subjected to research that code switching and code-mixing found in the Indonesian language learning in class X and XI in SMK Muhammadiyah 2 Surakarta academic year 2015/2016. Analysis of the data used in this study is an interactive model. The results showed that over the Indonesian code to the Java language is a shift from the use of Indonesian be the use of the Java language. Code switching from Indonesian to Javanese pretty much are in the process of learning Indonesian in class X and XI SMK Muhammadiyah 2 Surakarta academic year 2015/2016. During the learning process also showed that the form of the transfer of code from the Java language into Indonesian. In the classroom interaction between teachers and students often insert code in the form of word utterances interfere with the goal of keeping the conversation more intimate. In the process of learning Indonesian in class X and XI SMK Muhammadiyah 2 Surakarta school year 2015/2016 also found the use of code-mixing in the form looping said.